Publication rate and research topics of studies in pediatric kidney transplantation - Patry, Christian; Cordts, Stephanie E.; Baumann, Lukas; Höcker, Britta; Fichtner, Alexander; Ries, Markus; Tönshoff, Burkhard (Pediatric transplantation, 2022)
BACKGROUND: The quality of medical care for pediatric kidney transplant recipients depends on sound evidence from published clinical trials. - METHODS: We examined the publication rate, time to publication, and factors associated with publication of studies in pediatric kidney transplantation registered on ClinicalTrials.gov from 1999 to 2020. - RESULTS: We identified 136 studies with an overall enrollment of 36255 study participants, of which only 58.8% have been published yet. Unpublished studies included data from 14 350 participants. The median time to publication was 25 months (range, 0-117) with a significantly shorter time to publication in more recent years. The most frequently investigated research topic was immunosuppressants (49.3%), followed by perioperative management (11.0%) and infectiology (10.3%). The percentage of published studies was highest for the topic steroid withdrawal (87.5%), followed by infectiology (78.6%), and nutrition, sports and quality of life (71.4%). Studies, which were co-funded by industry, showed a significantly higher 5-year publication rate (p = 0.019). - CONCLUSIONS: In conclusion, nearly half of all studies in pediatric kidney transplantation remain unpublished. Non-publication of studies might lead to a publication bias with a negative impact on clinical decision-making.
Gesehen am 08.03.2022